Cartels and rent sharing at the farmer-trader interface: An example from Ghana's tomato sector - Robinson, Elizabeth J. Z.; Ngeleza, Guyslain K. (International Food Policy Research Institute, 2011)
Ghana's “market queens,” itinerant traders who purchase tomatoes from rural farms and bring them to the large urban markets, are accused of acting as a cartel, both driving down the price farmers receive and driving up the price urban consumers pay through restricting the volume of tomatoes entering key markets. Our paper provides the first detailed exploration of the interface between farmers and traders, combining a theoretical model with novel empirical data on daily prices and tomato quality that we collected from Ghana's Upper East region. We find evidence that the traders do operate a cartel but that farmers who sell to them receive higher prices than if they sell to the local market, even though there is little difference in quality compared with tomatoes sold to the local market. This suggests that traders share cartel rents with these farmers, resulting in lower prices in rural areas, higher prices in the cities, and a greater constriction of total market volume. Our paper suggests that policymakers would do better to focus on the full value chain and on opening up the urban markets rather than on strengthening farmers' bargaining power with the traders, which restricts market volumes and harms farmers unable to sell to traders.